Human Mpn1 promotes post‐transcriptional processing and stability of U6atac. Issue 18 (23rd July 2015) - Shchepachev, Vadim; Wischnewski, Harry; Soneson, Charlotte; Arnold, Andreas W.; Azzalin, Claus M.
Abstract : Mpn1 is an exoribonuclease that modifies the spliceosomal small nuclear RNA (snRNA) U6 by trimming its oligouridine tail and introducing a cyclic phosphate group (>p). Mpn1 deficiency induces U6 3′ end misprocessing, accelerated U6 decay and pre‐mRNA splicing defects. Mutations in the human MPN1 gene are associated with the genodermatosis Clericuzio‐type poikiloderma with neutropenia (PN). Here we present the deep sequencing of the >p‐containing transcriptomes of mpn1 Δ fission yeast and PN cells. While in yeast U6 seems to be the only substrate of Mpn1, human Mpn1 also processes U6atac snRNA. PN cells bear unstable U6atac species with aberrantly long and oligoadenylated 3′ ends. Our data corroborate the link between Mpn1 and snRNA stability suggesting that PN could derive from pre‐mRNA splicing aberrations. Abstract : Mpn1 RNase trims U6atac snRNA in humans. Aberrant U6atac accumulates in human cells carrying mutations in the MPN1 gene. Mpn1 counteracts 3′ adenylation of U6atac. Mpn1 promotes U6atac stability.